Single center study investigating the clinical association of donor-derived cell-free DNA with acute outcomes in lung transplantation - Noda, Kentaro; Snyder, Mark E.; Xu, Qingyong; Peters, David; McDyer, John F.; Zeevi, Adriana; Sanchez, Pablo G. (Frontiers in Transplantation, 2024)
Background: Circulating donor-derived cell-free DNA (dd-cfDNA) levels have been proposed as a potential tool for the diagnosis of graft injury. In this study, we prospectively investigated dd-cfDNA plasma levels and their association with severe primary graft dysfunction (PGD) and graft rejection after lung transplant.Methods: A total of 40 subjects undergoing de-novo lung transplants at our institution were recruited in this study. Blood samples were collected at various time points before and after lung transplant for 1 year. Dd-cfDNA in samples was determined using AlloSure assay (CareDx Inc.).The correlation of the value of %dd-cfDNA was investigated with the incidence of PGD, acute cellular rejection (ACR), and donor-specific antibody.We observed a rapid increase of %dd-cfDNA in the blood of recipients after lung transplantation compared to baseline. The levels of dd-cfDNA decreased during the first two weeks. The peak was observed within 72 hours after transplantation. The peak values of %dd-cfDNA varied among subjects and did not correlate with severe PGD incidence. We observed an association between levels of %dd-cfDNA from blood collected at the time of transbronchial biopsy and the histological diagnosis of ACR at 3 weeks.Our data show that circulating dd-cfDNA levels are associated with ACR early after transplantation but not with severe PGD. Plasma levels of dd-cfDNA may be a less invasive tool to estimate graft rejection after lung transplantation however larger studies are still necessary to better identify thresholds.